A chromosome-scale genome assembly of Castanopsis hystrix provides new insights into the evolution and adaptation of Fagaceae species - Huang, Wei-Cheng; Liao, Borong; Liu, Hui; Liang, Yi-Ye; Chen, Xue-Yan; Wang, Baosheng; Xia, Hanhan (Frontiers in Plant Science, 2023)
Fagaceae species dominate forests and shrublands throughout the Northern Hemisphere, and have been used as models to investigate the processes and mechanisms of adaptation and speciation. Compared with the well-studied genus Quercus, genomic data is limited for the tropical-subtropical genus Castanopsis. Castanopsis hystrix is an ecologically and economically valuable species with a wide distribution in the evergreen broad-leaved forests of tropical-subtropical Asia. Here, we present a high-quality chromosome-scale reference genome of C. hystrix, obtained using a combination of Illumina and PacBio HiFi reads with Hi-C technology. The assembled genome size is 882.6 Mb with a contig N50 of 40.9 Mb and a BUSCO estimate of 99.5%, which are higher than those of recently published Fagaceae species. Genome annotation identified 37,750 protein-coding genes, of which 97.91% were functionally annotated. Repeat sequences constituted 50.95% of the genome and LTRs were the most abundant repetitive elements. Comparative genomic analysis revealed high genome synteny between C. hystrix and other Fagaceae species, despite the long divergence time between them. Considerable gene family expansion and contraction were detected in Castanopsis species. These expanded genes were involved in multiple important biological processes and molecular functions, which may have contributed to the adaptation of the genus to a tropical-subtropical climate. In summary, the genome assembly of C. hystrix provides important genomic resources for Fagaceae genomic research communities, and improves understanding of the adaptation and evolution of forest trees.